Vitamin C fortification: need and recent trends in encapsulation technologies - Maurya, Vaibhav Kumar; Shakya, Amita; McClements, David Julian; Srinivasan, Ramachandran; Bashir, Khalid; Ramesh, Thiyagarajan; Lee, Jintae; Sathiyamoorthi, Ezhaveni (Frontiers in Nutrition, 2023)
The multifaceted role of vitamin C in human health intrudes several biochemical functions that are but not limited to antioxidant activity, homoeostasis, amino acid synthesis, collagen synthesis, osteogenesis, neurotransmitter production and several yet to be explored functions. In absence of an innate biosynthetic pathway, humans are obligated to attain vitamin C from dietary sources to maintain its optimal serum level (28 µmol/L). However, a significant amount of naturally occurring vitamin C may deteriorate due to food processing, storage and distribution before reaching to the human gastrointestinal tract, thus limiting or mitigating its disease combating activity. Literature acknowledges the growing prevalence of vitamin C deficiency across the globe irrespective of geographic, economic and population variations. Several tools have been tested to address vitamin C deficiency, which are primarily diet diversification, biofortification, supplementation and food fortification. These strategies inherit their own advantages and limitations. Opportunely, nanotechnology promises an array of delivery systems providing encapsulation, protection and delivery of susceptible compounds against environmental factors. Lack of clear understanding of the suitability of the delivery system for vitamin C encapsulation and fortification; growing prevalence of its deficiency, it is a need of the hour to develop and design vitamin C fortified food ensuring homogeneous distribution, improved stability and enhanced bioavailability. This article is intended to review the importance of vitamin C in human health, its recommended daily allowance, its dietary sources, factors donating to its stability and degradation. The emphasis also given to review the strategies adopted to address vitamin c deficiency, delivery systems adopted for vitamin C encapsulation and fortification.